Resilience and sustainability of hydraulic structures: the role of numerical simulation as an early warning tool for structural integrity assessment - Muhamad Bashar, Nur Azwa; Mohd Arif Zainol, Mohd Remy Rozaini; Mohd Radzi, Mohd Rashid (Unit Penerbitan PKAPP, 2025)
Hydraulic structures such as dams play a major role in the sustainable storage of clean water for daily use, irrigation, flood defence systems and the sustainable supply of electricity generation. Therefore, these structures should be preserved from external and internal impacts, e.g. natural hazards (earthquakes and floods), mechanical vibrations (pumps and turbines), sedimentation due to high velocities and fluid structures (flow-induced vibrations) (Ahmad Mazlan et al., 2020; Al-Obaidi, 2020; Alcocer-Yamanaka et al., 2020; Antoine et al., 2020). The tall and huge dam, which is also ageing and located in an earthquake-prone area with obvious structural deficiencies, is the most affected and prone to catastrophic structural failure (Adamo et al., 2020; Zhuang et al., 2019). Several dam failure events, such as the failure of the Oroville and Toddbrook spillways due to high-velocity water during prolonged rainfall and flooding, flow-induced vibrations due to earthquakes and material fatigue, have highlighted the urgent need for predictive and adaptive approaches to assess dam safety (Balmforth, 2020; France et al., 2018; Goodling et al., 2018; Heidarzadeh & Feizi, 2022; Hollins et al., 2018; Hughes, 2020; Koskinas et al., 2019; Stelloh et al., 2017; Vahedifard et al., 2017; White et al., 2019). Therefore, a well-equipped monitoring system, especially for seismic and structural damage, is crucial as an early warning system and as a basis for the selection of appropriate non-structural or structural measures to extend design and operational life. An example of a well-equipped seismic and structural condition monitoring system is the Cabril Dam in Portugal, which is capable of detecting dynamic vibrations (seismic behaviour during earthquake event) (Oliveira & Alegre, 2020). The International Committee on Large Dams (ICOLD) has pointed out that high-risk dams must be regularly inspected for structural integrity to ensure the best structural condition and safety. This is supported by the member countries, including Malaysia, through the National Committee on Large Dams (MYCOLD). The management and evaluation of the condition of dams in Malaysia was carried out using the specific checklist of the Malaysia Dam Safety Guidelines (MyDAMS). MyDAMS was prepared by MYCOLD members who are representatives of dam owners, operators, government agencies involved in dam management/issues and dam practitioners in Malaysia. Several dams were inspected and assessed in the Malaysian landscape, including the Muda and Ahning Dams (Kedah), the Jor and Mahang Dams (Perak), the Sultan Abu Bakar Dam (Pahang), the Babagon Dam (Sabah), the Bakun Dam (Sarawak) and the Kenyir Dam (Terengganu). Problems investigated included structural integrity (e.g. concrete cracking and deterioration), soil erosion, landslides and severe collapse potential (BERNAMA, 2023).